2013
DOI: 10.15376/biores.8.2.2998-3016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Water Uptake as Function of Surface Modification of Empty Fruit Bunch Oil Palm Fibres in PP Biocomposites

Abstract: Empty fruit bunch oil palm (EFBOP) fibres were surface modified by four different methods, propionylation, vinyltrimethoxy silanization, PPgMA dissolution modification, and PPgMA blending, and integrated into a polypropylene (PP) matrix. The designed biocomposites were subjected to an absorption process at different temperatures. Their water uptake behaviour was compared with the unmodified fibre biocomposites. An increased fibre content and temperature resulted in increased water uptake for all of the biocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…It is clear that all the composites exhibit a Fickian diffusion, as the value of n is found close to 0.5. These findings are in agreement with the literature . The value of k gives an offer of the contact of water with composites .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It is clear that all the composites exhibit a Fickian diffusion, as the value of n is found close to 0.5. These findings are in agreement with the literature . The value of k gives an offer of the contact of water with composites .…”
Section: Resultssupporting
confidence: 92%
“…Therefore, the lowest value of P c was seen for composite SC (T2) followed by composites SC (T1) and SC. The calculated values of water absorption kinetics parameters such as diffusion, corrected diffusion, sorption, and permeability coefficients for pure and modified sisal composites are summarized in Table …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the alkaline treatment can remove impurities from the surface of the filler and hence such roughening may produce an improvement in the wettability property with PP matrix. 8 Thus, the NaOH-treated composites had better adhesion than untreated composites. Hence, the results of tensile strength of NaOH-treated composites were found to be better than untreated composites and were supported by this testing.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 93%
“…Thus, alkaline treatment will directly affect the cellulosic fibril and degree of polymerization of lignin and hemicellulosic compounds. 7,8 It was found that alkaline treatment has two effects on the fiber: It is capable of increasing surface roughness and increases the number of possible reaction sites exposed on the fiber surface. There explains the reinforcement phenomenon of mechanical properties with NaOH-treated fiber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation